Sustainable Marketing of Ukrainian Agricultural Enterprises to Enter Global Grain Markets - Belkin, Ihor; Trapaidze, Sofiia; Bondarenko, Valerii; Omelianenko, Oleksandr; Cherniavskyi, Ivan (European Journal of Sustainable Development, 2025)
The article provides a study of current issues regarding the role of Ukraine in the world grain trade and the challenges caused by current conditions. The potential of the Ukrainian grain market and its position against the background of global ratings of producers and exporters are analyzed. Key risks for the grain sector are identified. The commodity and geographical structure of grain exports during wartime is studied, and the strategic importance of Ukrainian grain for ensuring global food stability is emphasized. The impact of the imbalance between supply and demand and fluctuations in world prices for grain crops is outlined. Price dynamics were analyzed and it was determined that the likely price increase could have serious consequences for global food markets, in particular for low-income countries that could face a food crisis. A set of measures aimed at minimizing the negative impact of the war on global food security, including in connection with a possible grain shortage and further price increases, has been proposed. Keywords: foreign market, grain, world exporter, economy, marketing strategies, agricultural sector, world community, food security.